Bona–Smith-Type systems in Bounded Domains with Slip-Wall Boundary Conditions: Theoretical Justification and a Conservative Numerical Scheme - Antonopoulos, Dimitrios; Mitsotakis, Dimitrios (Journal of scientific computing, 2025)
Considered herein is a class of Boussinesq systems of Bona–Smith type that describe the propagation of long surface water waves of small amplitude in bounded two-dimensional domains with slip-wall boundary conditions and variable bottom topography. Such boundary conditions are necessary in situations involving water waves in channels, ports, and generally in basins with solid boundaries. We prove that, given appropriate initial conditions, the corresponding initial-boundary value problems have unique solutions locally in time, which is a fundamental property of deterministic mathematical modeling. Moreover, we demonstrate that the systems under consideration adhere to three basic conservation laws for water waves: mass, vorticity, and energy conservation. The theoretical analysis of these specific Boussinesq systems leads to a conservative mixed finite element formulation. Using explicit, relaxation Runge–Kutta methods for the discretization in time, we devise a fully discrete scheme for the numerical solution of initial-boundary value problems with slip-wall conditions, preserving mass, vorticity, and energy. Finally, we present a series of challenging numerical experiments to assess the applicability of the new numerical model.